Best practices in justifying calibrations for dating language families - Maurits Luke; de Heer Mervi; Honkola Terhi; Dunn Michael; Vesakoski Outi (Oxford University Press, 2022)
The use of computational methods to assign absolute datings to language divergence is receiving renewed interest, as modern approaches based on Bayesian statistics offer alternatives to the discredited techniques of glottochronology. The datings provided by these new analyses depend crucially on the use of calibration, but the methodological issues surrounding calibration have received comparatively little attention. Especially, underappreciated is the extent to which traditional historical linguistic scholarship can contribute to the calibration process via loanword analysis. Aiming at a wide audience, we provide a detailed discussion of calibration theory and practice, evaluate previously used calibrations, recommend best practices for justifying calibrations, and provide a concrete example of these practices via a detailed derivation of calibrations for the Uralic language family. This article aims to inspire a higher quality of scholarship surrounding all statistical approaches to language dating, and especially closer engagement between practitioners of statistical methods and traditional historical linguists, with the former thinking more carefully about the arguments underlying their calibrations and the latter more clearly identifying results of their work which are relevant to calibration, or even suggesting calibrations directly.